Engineering collaborations for accessing hidden web resources - Sehgal, Manpreet Singh (PREPARE@u® | IEI Conferences, 2021)
The world wide web has always been a research platform for information and data scientists. The value of information is generally seen as a proportional to the depth of the world wide web. While the surface web is being taken good care of by the search engines at a great length, It is the deep web that posed challenges to the information and data scientists. A lot of research has been expended in the direction of extracting information from the deep web resources. Many researchers have studied the problem statement in their perspective and devise solutions to address their formulated problem statements. Individually these efforts showed promising results. However, there has been a gap of the joint effort to bring these individual efforts together to reap the collective fruits to address the much larger and more sensible problem statement. This paper highlights the different problem statements of different researchers and suggests the collaborative approach to bring out one common problem statement to envisage one big problem and its probable solution.